Helicobacter cinaedi bacteremia in a returning traveler. (2020) - Fox-Lewis, Andrew; Basu, Indira; Vesty, Anna; Henderson, Gillian; Chhibber, Aakash V.; Thomas, Mark
Abstract: Of the non‐ Helicobacter pylori Helicobacter (NHPH) species, Helicobacter cinaedi is an emerging cause of infection in humans. Here we report a novel clinical presentation of H. cinaedi infection: a case of fever in a returning traveler. A 31 year old previously fit and well male presented with onset of fever 24 h after returning from travel in Singapore and Indonesia. Associated symptoms consisted of sore throat, mild shortness of breath, generalized myalgia and arthralgia, headache, and four episodes of loose stools. The patient recovered spontaneously without treatment and was discharged. After 4 days of incubation, blood cultures grew H. cinaedi . H. cinaedi is a slow-growing fastidious organism poorly detected by some commonly used automated blood culture systems, and difficult to identify using commercial or traditional biochemical identification systems. This case illustrates the importance of H. cinaedi as an emerging pathogen in immunocompetent patients, with a wide variety of possible clinical presentations. The challenges in the microbiological diagnosis of H. cinaedi infections lead us to speculate that H. cinaedi is an underdiagnosed cause of febrile illness, both in returning travelers and in other clinical settings.